Thioredoxins: Emerging Players in the Regulation of Protein S-Nitrosation in Plants - Tereza Jedelská; Lenka Luhová; Marek Petřivalský (Plants, 2020)
S-nitrosation has been recognized as an important mechanism of ubiquitous posttranslational modification of proteins on the basis of the attachment of the nitroso group to cysteine thiols. Reversible S-nitrosation, similarly to other redox-based modifications of protein thiols, has a profound effect on protein structure and activity and is considered as a convergence of signaling pathways of reactive nitrogen and oxygen species. This review summarizes the current knowledge on the emerging role of the thioredoxin-thioredoxin reductase (TRXR-TRX) system in protein denitrosation. Important advances have been recently achieved on plant thioredoxins (TRXs) and their properties, regulation, and functions in the control of protein S-nitrosation in plant root development, translation of photosynthetic light harvesting proteins, and immune responses. Future studies of plants with down- and upregulated TRXs together with the application of genomics and proteomics approaches will contribute to obtain new insights into plant S-nitrosothiol metabolism and its regulation.